2023
DOI: 10.3390/ijms24066002
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Metabolism and EV Cargo of Endothelial Cells Is Affected in Presence of EVs Derived from MSCs on Which HIF Is Activated

Abstract: Small extracellular vesicles (sEVs) derived from mesenchymal stem cells (MSCs) have attracted growing interest as a possible novel therapeutic agent for the management of different cardiovascular diseases (CVDs). Hypoxia significantly enhances the secretion of angiogenic mediators from MSCs as well as sEVs. The iron-chelating deferoxamine mesylate (DFO) is a stabilizer of hypoxia-inducible factor 1 and consequently used as a substitute for environmental hypoxia. The improved regenerative potential of DFO-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Research has shown that at appropriate concentrations and action times, DFO could actively affect multiple stages of peripheral nerve regeneration in Schwann cells, thereby improving the effectiveness of nerve injury repair . Mesenchymal cells treated with low concentrations of DFO induce molecular pathways and biological processes closely related to proliferation and angiogenesis in recipient endothelial cells . This indicated that the different effects of DFO in different cells are closely related to its dosage and time of action and the research purpose.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Research has shown that at appropriate concentrations and action times, DFO could actively affect multiple stages of peripheral nerve regeneration in Schwann cells, thereby improving the effectiveness of nerve injury repair . Mesenchymal cells treated with low concentrations of DFO induce molecular pathways and biological processes closely related to proliferation and angiogenesis in recipient endothelial cells . This indicated that the different effects of DFO in different cells are closely related to its dosage and time of action and the research purpose.…”
Section: Discussionmentioning
confidence: 89%
“…64 Mesenchymal cells treated with low concentrations of DFO induce molecular pathways and biological processes closely related to proliferation and angiogenesis in recipient endothelial cells. 65 This indicated that the different effects of DFO in different cells are closely related to its dosage and time of action and the research purpose. Further research is needed to determine whether DFO alleviates OTA-inhibited cell proliferation in myoblasts.…”
Section: Ferroptosismentioning
confidence: 99%
“…Exosomes act as messengers in the process of intercellular communication at a paracrine and endocrine level 5 , interacting with cells (as established in Figure 4 ) and transferring their cargo to recipient cells - thus changing their phenotype or regulating gene expression 14 . The exosome loading is sorted by ESCRT-dependent and independent mechanisms, and it is influenced by the parental cell and environmental characteristics 14 , 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes play a major role in cell-cell communication both at a paracrine and systemic level. They are involved in either physiological processes (i.e., immune response, cell proliferation, and differentiation) or pathological ones (i.e., cancer progression, cardiovascular diseases) 1 , 4 , 5 . Exosomes contain nucleic acids, proteins, lipids, and other metabolites that are secreted by donor cells and taken up by recipient cells.…”
Section: Introductionmentioning
confidence: 99%
“…Zanotti et al explored the effects of sEVs released from DFO-treated ASCs (DFO-sEVs) on human umbilical vein endothelial cells (HUVECs). The authors used transcriptome sequencing and miRNA profiling of the sEV cargo (sEV-miRNA) of treated HUVECs and found significant enhancement of mitochondrial oxidative phosphorylation [ 9 ].…”
mentioning
confidence: 99%